MO198IMPACT OF KIDNEY FUNCTION ON THE EVOLUTION OF MONOCLONAL GAMMOPATHIES OF UNCERTAIN SIGNIFICANCE. (29th May 2021) - Gil Giraldo, Yohana; Muñoz Ramos, Patricia; Sanchez, Ana; Cabrera, Alicia; Quiroga, Borja
Abstract: Background and Aims: Monoclonal gammopathies of uncertain significance (MGUS) are very prevalent, but neoplastic transformation barely reaches 1% per year. Renal involvement in the course of a MGUS is a risk factor for complications. The objective of our study is to determine the prognosis of MGUS that present renal deterioration during their evolution. Method: In the present retrospective cohort study, MGUS cases from our center were included. Baseline epidemiological and comorbidity data were collected (including renal function and hematological parameters). At 6 and 12 months, data on renal function and proteinuria were collected. During the follow-up, fatal events and the need for renal replacement therapy (RRT) were recorded as a combined endopoint. Associated factors to this combined endpoint were evaluated. Results: One hundred twenty patients (47% women, age 81±9 years.) with diagnosis of MGUS were included. Of these, 61 (51%) had renal involvement at the time of diagnosis and 16 (13%) had an estimated glomerular filtration rate (eGFR) of less than 60 ml/min/1.73m 2 during follow up. Associated factors with presenting eGFR less than 60 ml/min/1.73m 2 were hypertension (p=0.001), peripheral vascular disease (p=0.05), age (p=0.05), Charlson comorbidity index (p<0.001), β2microglobulin (p = 0.002), baseline proteinuria (p <0.001) and baseline renal function (p <0.001). During follow-up (median 41 [20-60] months), 34 patients (28%) presented the combined event (8 required RRT and 28 died). The presence of an eGFR less than 60 ml /min/1.73m 2 during the first year of follow-up was associated with the combined event (p = 0.028) (Figure 1 ). In a multivariate model adjusted for age, sex and baseline CKD, the presence of a determination of eGFR lower than 60 ml/min/1.73m 2 was an independent predictor for the combined event (HR 3.9 [95% CI 1.4-11.3], p = 0.009). In patients without chronic kidney disease at baseline, 13 (22%) combined events were reported. The incidence of a determination of eGFR lower than 60 ml/min/1.73m 2 was associated with the combined event during follow-up (p = 0.012). In a multivariate model adjusted for age and Charlson index, presenting an eGFR lower than 60 ml/min/1.73m 2 was an independent predictor for the combined event (HR 6.7 [95% CI 1.7-26.7], p = 0.007) (Figure 2 ) Conclusion: Among patients with MGUS, the presence of eGFR lower than 60 ml/min/1.73m 2 is independently associated with a higher incidence of RRT and/or mortality.